Targeted Therapy With Immunoconjugates for Multiple Myeloma - Bruins, Wassilis S. C.; Zweegman, Sonja; Mutis, Tuna; van de Donk, Niels W. C. J. (Frontiers in Immunology, 2020)
The introduction of proteasome inhibitors (PI) and immunomodulatory drugs (IMiD) has markedly increased the survival of multiple myeloma (MM) patients. Also, the unconjugated monoclonal antibodies (mAb) daratumumab (anti-CD38) and elotuzumab (anti-SLAMF7) have revolutionized MM treatment given their clinical efficacy and safety, illustrating the potential of targeted immunotherapy as a powerful treatment strategy for MM. Nonetheless, most patients eventually develop PI-, IMiD-, and mAb-refractory disease because of the selection of resistant MM clones, which associates with a poor prognosis. Accordingly, these patients remain in urgent need of new therapies with novel mechanisms of action. In this respect, mAbs or mAb fragments can also be utilized as carriers of potent effector moieties to specifically target surface antigens on cells of interest. Such immunoconjugates have the potential to exert anti-MM activity in heavily pretreated patients due to their distinct and pleiotropic mechanisms of action. In addition, the fusion of highly cytotoxic compounds to mAbs decreases the off-target toxicity, thereby improving the therapeutic window. According to the effector moiety, immunoconjugates are classified into antibody-drug conjugates, immunotoxins, immunocytokines, or radioimmunoconjugates. This review will focus on the mechanisms of action, safety and efficacy of several promising immunoconjugates that are under investigation in preclinical and/or clinical MM studies. We will also include a discussion on combination therapy with immunoconjugates, resistance mechanisms, and future developments.